Bacterial activation of epithelial signaling - Prince, Alice (Henry Stewart Talks, 2021)
Bacterial interactions with epithelium, Cystic fibrosis (CF) model, Pathogens in CF, Pseudomonas aeruginosa adaptations, CFTR and PTEN dysfunction, Long term bacterial mutations, Host-pathogen interactions, Pseudomonas aeruginosa in CF